Evaluation of the Child Safety Matters Curriculum for Improving Knowledge about Victimization among Elementary School Children: A Randomized Trial. Issue 8 (17th November 2021) - Weeks, Erin A.; Whitaker, Daniel J.; Pendarvis, Stacy; Finkelhor, David; Neal-Rossi, Carol; Rivers, Danielle
ABSTRACT: This project employed a randomized-control design to evaluate the effectiveness of the MBF Child Safety Matters® (CSM) curriculum. Six Georgia schools across 3 counties agreed to participate, and 136 K – 5th grade classrooms were randomized to either receive the CSM curriculum or be a wait-list control and to receive the curriculum after the evaluation. In total, 2, 414 students participated at pretest (1195 CSM and 1219 control) and 2, 260 participated at posttest (1159 CSM and 1101 control). Pre/posttests were collected from all students prior to the delivery of the CSM curriculum and again approximately a month later to measure knowledge gains related to child safety. Intervention students displayed a greater increase in knowledge for the information taught in the CSM program as compared to students who did not receive the intervention (d = .29).